(untitled) (مجلة جامعة اللاذقية- سلسلة العلوم الاقتصادية والقانونية, 2018)
The objective of this study is to assess the reality of the professional commitment of the employees in the private commercial banks in lattakia Governorate, The researchers identified three types of functional commitment, which included both Affective commitment, Continuance commitment, and Normative commitment. The researchers distributed a questionnaire to a random sample of 77 workers. Each questionnaire included 24 phrases that measured the three types of commitment. They calculated the Cronbach’s Alpha coefficient to measure the stability of the scale, The t-test was used for one sample to test the hypotheses, The researchers found results showing high degrees of functional commitment of all three types, but at varying degrees, where the mean of the responses on the expressions that measured the three types of commitment was Greater than the mean neutrality of the scale. يهدف هذا البحث إلى تقويم واقع الالتزام الوظيفي لدى العاملين في المصارف التجارية الخاصة في محافظة اللاذقية، حيث قام الباحثان بتحديد ثلاثة أنواع من الالتزام الوظيفي لدى العاملين في تلك المصارف, شملت كل من الالتزام العاطفي، والالتزام المستمر، والالتزام المعياري. وقد قام الباحثان بتوزيع استبانة على عينة عشوائية من العاملين بلغت /77/مفردة، تضمنت كل استبانة/24/ عبارة، تقيس مستوى الأنواع الثلاثة من الالتزام، وقاما باختبار مدى ثبات المقياس المستخدم اعتماداً على معامل ألفا كرونباخ، واستخدما اختبار t ستيودينت لعينة واحدة لاختبار الفرضيات، وقد توصل الباحثان إلى نتائج تبيّن وجود مستويات عالية من الالتزام الوظيفي بأنواعه الثلاثة ولكن بدرجات متفاوتة, حيث كان متوسط الاجابات على العبارات التي تقيس أنواع الالتزام الثلاثة أكبر من متوسط الحياد للمقياس.